1999
DOI: 10.1074/jbc.274.40.28256
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Regulatory Sequences and Binding Proteins in the Type II Sodium/Phosphate Cotransporter NPT2 Gene Responsive to Dietary Phosphate

Abstract: Dietary phosphate (P i ) is a most important regulator for renal P i reabsorption. The type II sodium-dependent phosphate (Na/P i ) cotransporters (NPT2) are located at the apical membranes of renal proximal tubular cells and major functional transporters associated with renal P i reabsorption. The consumption of a low-P i diet induces the synthesis of NPT2, whereas a high P i diet decreases it. The molecular mechanisms of regulation by dietary P i are not yet known.In this report, in weaning mice fed a low-P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 35 publications
(57 reference statements)
2
53
1
Order By: Relevance
“…In mice responding to increases and decreases in phosphate intake, a PO4 response element has been reported in the NPT2a gene, and an associated transcription factor, mE3, has been identified. 23 Nevertheless, it remains unclear whether the most proximal phosphate sensing signal is extracellular or intracellular. 24 Uncertainties remain regarding PO4 sensing mechanisms in the parathyroid gland, osteocytes/osteoblasts, and renal cortical 1a-hydroxylase.…”
mentioning
confidence: 99%
“…In mice responding to increases and decreases in phosphate intake, a PO4 response element has been reported in the NPT2a gene, and an associated transcription factor, mE3, has been identified. 23 Nevertheless, it remains unclear whether the most proximal phosphate sensing signal is extracellular or intracellular. 24 Uncertainties remain regarding PO4 sensing mechanisms in the parathyroid gland, osteocytes/osteoblasts, and renal cortical 1a-hydroxylase.…”
mentioning
confidence: 99%
“…Using the MC3T3-E1 osteoblast differentiation model (1-3), we have recently described the significance of inorganic phosphate, which is generated during differentiation, as a signaling molecule capable of altering specific signal transduction pathways, gene expression, and ultimately mineralization (4,5). Furthermore, a number of studies have demonstrated the ability of inorganic phosphate to alter gene expression and or cell function in other cell types, including parathyroid (6), neurons (7), kidney (8), vascular smooth muscle (9), chondrocytes (10), and osteoclasts (11). Hence, a more complete understanding of the consequences of elevated inorganic phosphate on cell function may be relevant not only to the process of osteoblast differentiation but also to various cell types with a wide range of functions.…”
mentioning
confidence: 99%
“…Thus it will be possible to conduct further in vivo studies using deletion and mutational constructs based on this promoter region to try to ascertain the cis-acting, and subsequently trans-acting, elements responsible for specifying proximal tubule expression and thereby gain insight with respect to differentiation of specialized nephron segments, during development, or in response to renal injury (such as in recovery from acute tubule necrosis). Although we and others have conducted such deletion and mutation analyses in cell culture (7,10,22,27), the transgenic model provides a superior opportunity for such analysis in an in vivo system.…”
Section: Discussionmentioning
confidence: 99%